Socially responsible investment in the 21st century does it make a difference for society? - Louche, Céline; Hebb, Tessa (Emerald, 2014)
Does Socially Responsible Investment (SRI) affect society in the 21st century? This book explores various facets of SRI to address its potential and limits to create societal change. Little research has been undertaken on the societal impacts of SRI. With this book we contribute to this debate, pushing the boundaries of SRI even further.
Includes index.
Keywords: Investments -- Moral and ethical aspects.; elektronické knihy; electronic books